The aims of this research are to analyse the optimal allocation rate of resources. utilization of pond culture, to estimate and to analyse land rent value of prawn pond culture and to estimate affect of change In exogeneous variable on the land rent value. Finding of the researcah shows that economic value of prawn pond culture of Tanjung Paslr village, Is estimated to be Rp163.864.380,95 and of Tanjung Baru village to be Rp192.484,85. Based on Ricardian land rent concept. tanjung Baru village h - M Prihatna Sobari; Suharno .; Dwi Sushanty (Buletin Ekonomi Perikanan, 2008)
The aims of this research are to analyse the optimal allocation rate of resources. utilization of pond culture, to estimate and to analyse land rent value of prawn pond culture and to estimate affect of change In exogeneous variable on the land rent value. Finding of the researcah shows that economic value of prawn pond culture of Tanjung Paslr village, Is estimated to be Rp163.864.380,95 and of Tanjung Baru village to be Rp192.484,85. Based on Ricardian land rent concept. tanjung Baru village has land rent value of Rp1.560.182,OO while Tanjung Paslr village has about Rp1.065.431,OO. Multiple regression model, applied for this research Indicates that1here Is a corelation between land rent value and produdivlty fadors and distance. the model has also shows that fador productivity has a positive correlation to the land rent value,.while distance has a negative correlation to the land rent value. It Is also indicated that Tanjung Baru village has reached almost an optimal condition. The finding of sentivity analysis shows that the increase of oil price and urea fertilize reduced the value of land rent and the magnitude of change in the value of land rent be affected by the fador of fertility rate and the distance of the pond location from the existing local spot market.